A QUALITATIVE STUDY: EVALUATION OF WAITING TIME IN REGISTRATION FROM HUMAN RESOURCES WITH MALCOM BALDRIGE APPROACH - Sukaria Susana Br. Ginting; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Backgound: Building a health system is one of the SDG targets – universal health coverage (UHC). Strong primary health care system needs to be in place (4). The critical issue is the quality of health by improving patient safety, effectiveness, focus on patients, timely, efficient and fair (4, 10). Long waiting times decreased utilization of national health insurance, decreased use by the public and the rising cost of health. (5,7,8,9). The aim of this paper is to investigate how the human resources can lead to long waiting times in the registration by using Malcolm Baldrige approach (6). Method: This study used qualitative design to describe waiting time problem and it’s causes. Informants were appropriately and adequately selected in relation to waiting time including patients clinic, staff and management so the information were triangulated by resources,by methods and by data itself. The results were write as transcription and content analysis carefully done to identify themes and problem. This study held at Public Health Center, Cariu, Bogor, Indonesia in December 2016. Results: All the informants expressed their concern related to waiting time and need to formulate effective solutions. The solutions were proposed related to causes to the waiting time ; no monitoring and evaluation effort to control waiting time and it’s impact, clinical safety procedures, unsatisfied patients and ineffective clinical outcomes ; low priority to human resources management; no supervision ; no on the job training; no evaluation of patients need and expectation, the public health center never had services design ; network instability and inflexibility in the provision of facilites. Conclusion: Monitoring and evaluation, human resources management, supervision, on the job training, strategic planning, patients focus , commitment and the leadership itself are needed to decrease waiting time.